Applying an ecosystem approach to explore modifiable factors related to the risk for low motor competence in young children. Issue 11 (November 2022) - Van Kann, D.H.H.; Koolwijk, P.; de Kok, T.; Vos, S.B.; de Vries, S.I.; Mombarg, R.; van Aart, I.; Savelsbergh, G.J.P.; Hoeboer, J.J.M.M.; Remmers, T.
Abstract: Objectives: Early childhood is a crucial phase for motor development in which differences between children can manifest. These differences might be related to factors in ecosystems in which children are raised, of which little is currently known. The current study's purpose was to explore which modifiable factors in children's ecosystems are associated with the odds for low versus higher motor competence (MC) in 4- to 6-year-old children. Design: A cross-sectional study design was conducted to investigate which modifiable social and physical factors in the home environment and direct living environment were associated with differences in MC. Methods: Children's MC was measured through the Athletic Skills Track in 612 4- to 6-year-olds, from 10 primary schools in Eindhoven, the Netherlands. Parenting practices, characteristics of the home environment, and perceptions of the direct living environment were assessed through parental questionnaires. Hierarchical logistic regression analyses were conducted to evaluate factors associated with low MC in children. Results: The presence of a garden at home and higher perceived sports facilities in the direct living environment decreased the likelihood of children being classified as low MC. Moreover, stronger parental active transportation routines and more discouraging physical activity parenting practices resulted in lower odds of low MC. In addition, girls were more at risk for low MC. Conclusions: Characteristics of the social and physical home environment and direct living environment were associated with MC disparities during early childhood. Both parenting practices and parental physical activity-involved behaviours are relevant modifiable factors related to differences in children's MC.